2016
DOI: 10.1063/1.4952444
|View full text |Cite
|
Sign up to set email alerts
|

Comparative atomic-scale hydration of the ceramide and phosphocholine headgroup in solution and bilayer environments

Abstract: Previous studies have used neutron diffraction to elucidate the hydration of the ceramide and the phosphatidylcholine headgroup in solution. These solution studies provide bond-length resolution information on the system, but are limited to liquid samples. The work presented here investigates how the hydration of ceramide and phosphatidylcholine headgroups in a solution compares with that found in a lipid bilayer. This work shows that the hydration patterns seen in the solution samples provide valuable insight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 57 publications
1
11
0
Order By: Relevance
“…This differs to DMSO that in the presence of C 3 -PC showed slight increased DMSO-water interactions 11 and it is properties such as these that could be indicative of PG having a less perturbing effect as a solvent on lipid structures compared to DMSO. 44 That the hydration observed here is highly consistent with that observed for the DOPC headgroup in a bilayer, 41 which in turn is highly similar to the solvation of C 3 -PC in solution, 12 suggests that the current measurements are significantly useful in determining the behavior of PG in membranes.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…This differs to DMSO that in the presence of C 3 -PC showed slight increased DMSO-water interactions 11 and it is properties such as these that could be indicative of PG having a less perturbing effect as a solvent on lipid structures compared to DMSO. 44 That the hydration observed here is highly consistent with that observed for the DOPC headgroup in a bilayer, 41 which in turn is highly similar to the solvation of C 3 -PC in solution, 12 suggests that the current measurements are significantly useful in determining the behavior of PG in membranes.…”
Section: Discussionsupporting
confidence: 78%
“…1) adjacent to the onium group and the surrounding water solvent. 11,12,41 This hydrogen bonding from water to this portion of the PC molecule is present in the current solutions, as the g HLOw (r) in Figure 5 (a) in both MD and EPSR fits to the diffraction data show a first peak at around 2.1Å with a coordination number of ∼0.6 hydrogen bonds (Table IV). This value is comparable to that observed in DMSO, where the coordination number was 0.5 for the EPSR simulation, 11 but still exhibits lower coordination of water compared to the 1 bond seen for pure water simulations.…”
Section: Figs 4 (D) and (E)mentioning
confidence: 68%
“…EPSR has been specifically designed in order to produce a computational model constrained to fit the experimental neutron diffraction data. 34,35 The use of EPSR to analyse neutron diffraction data has been frequently exploited to study the solution properties of a range of organic liquids, 11,12,14,[36][37][38][39][40][41][42][43][44][45][46] biological and drug molecules [47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62] and ionic species. [63][64][65][66] A set of reference potentials are used to start the EPSR process and these potentials are subsequently modified to provide a fit to the neutron diffraction data through a reverse Monte Carlo process.…”
Section: B Empirical Potential Structure Refinementmentioning
confidence: 99%
“…46,47 Here, a set of orthonormal coordinates were assigned to both the water molecules, chloroform and different portions of the DOPE molecules (see SI Figure 2) to assess the 3-dimensional hydration structure around the DOPE headgroup by virtue of Spatial Density Maps (SDMs) vide infra. For EPSR, 5312 configuration files were collected for the subsequent analysis and 4005 snapshots of the MD trajectory were used as a comparison, comparable to number of frames used in ANGULA analyses on other lipids 11,14 . The maps show the location of molecules around a central group, with the scale bar representing the density of atoms perÅ 3 for a specified distance range and percentage.…”
Section: F Angulamentioning
confidence: 99%
“…10 Importantly, it has been recently shown that hydration studies of headgroups in such solutions serve as a good predictor of the hydration behavior within a membrane. 11 This combination of experimental and computational techniques have also been used to characterize the hydration of other prominent lipid headgroups which are present within biological membranes -including the PC headgroup, [12][13][14] and the sphingolipid ceramide 10 . This multidisciplinary approach is ideal for determining the atomic scale interactions between lipids and the surrounding aqueous solvents.…”
Section: Introductionmentioning
confidence: 99%